Noncanonical NF-κB signaling in microvessels of atherosclerotic lesions is associated with inflammation, atheromatous plaque morphology and myocardial infarction. (March 2018) - Maracle, Chrissta X.; Agca, Rabia; Helder, Boy; Meeuwsen, John A.L.; Niessen, Hans W.M.; Biessen, Erik A.L.; de Winther, Menno P.J.; de Jager, Saskia C.A.; Nurmohamed, Mike T.; Tas, Sander W.
Abstract: Background and aims: Neovascularization is associated with atherosclerotic plaque instability and increased chance of myocardial infarction (MI). Patients with chronic inflammatory diseases (CID) have increased risk of atherosclerosis, and evidence demonstrates that NF-κB inducing kinase (NIK)-mediated noncanonical NF-κB signaling in endothelial cells (EC) is linked to inflammation and angiogenesis. Here, we hypothesized NIK may also be activated in EC of atherosclerotic lesion microvessels. Methods: Using cohorts of atherosclerotic lesions from coronary and carotid arteries, we quantified NIK expression in plaque microvessels and compared it to pathological markers, including inflammatory cell content, plaque characteristics and MI. Differences in gene transcripts were evaluated between stable and ruptured lesions. Results: NIK + EC were present in both coronary and carotid lesions. In CID patients, plaques with stenosis >40% had an increased number of NIK + EC and higher content of immune cells ( p  < .05) as compared to controls. Immune cells per NIK + EC were also greater in CID patients ( p  < .05), with pronounced differences as stenosis increased. In unstable lesions, NIK + EC were elevated as were EC expressing CXCL12 ( p  < .05). NIK + EC were increased in lesions with lipid content >40% ( p  < .05) and more abundant in coronary artery lesions implicated in MI ( p  < .05). These vessels also associated with atheromatous rather than fibrous plaque morphology ( p  < .05). Transcriptomic profiling demonstrated components of noncanonical NF-κB pathway were also upregulated in ruptured plaques ( p  < .05). Conclusions: NIK + EC associate with chronic inflammation in advanced lesions and are linked to markers of local inflammation, lipid content, unstable plaque phenotype and development of MI. Therefore, targeting noncanonical NF-κB signaling may hold therapeutic potential for patients with atherosclerosis and cardiovascular disease. Highlights: Microvessels in atherosclerotic lesions are characterized by active noncanonical NF-κB signaling with stable NIK expression. Chronic inflammatory disease patients exhibit increased NIK + microvessels in lesions with stenosis greater than 40%. NIK + microvessels significantly correlate with inflammatory cell content of plaques. NIK expression in endothelial cells is linked to neovascularization and plaque instability. NIK + microvessels associate to fatty, atheromatous plaques and are elevated in arteries implicated in myocardial infarction.